Progress of research on emergency triage of patients with chest pain (急诊胸痛患者预检分诊的研究进展) - LI Jinghuan (李靖嬛); YAO Weihai (姚卫海); LI Xiang (李想); ZHANG Qingchen (张清晨); GAO Wei (高伟) (中西医结合护理)
Triage　is the scientific process of sorting patients as they present to the emergency care setting, and is one key strategy used to ensure reduce the modality and disability. Aim of triage is to correctly identify patients and guide them to rapid and correct treatment. This paper reviewed the researches on emergency triage of patients with chest pain, and provided reference for quality of triage in emergency care. (急诊科预检分诊是用科学的方法将患者进行分类, 迅速识别急、危、重患者, 使之得到及时有效的救治, 减少患者死亡或伤残的发生。快速正确的急诊预检分诊是急性胸痛患者得到及时有效治疗的保证。本文就急性胸痛预检分诊工作进行综述, 旨在为提高护理预检分诊工作质量提供参考。)